2022
DOI: 10.14522/darwiniana.2022.101.953
|View full text |Cite
|
Sign up to set email alerts
|

A nomenclatural conspectus of Waltheria (Malvaceae, Byttnerioideae) in Brazil

Abstract: A nomenclatural conspectus is presented for the species of Waltheria (Malvaceae: Byttnerioideae) that occur in Brazil. Synonymies for 33 species, 23 endemic, are presented. Seven names are newly synonymized. In addition, eight excluded or unresolved names are discussed. Thirty-nine lectotypes are designated for Waltheria names, one neotype is designated for the name of an Astropus species, and two lectotypes for Visenia. These last two lectotypifications supersede previous ones, which misinterpreted and confus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…In Brazil, W. rotundifolia occurs only in the northeastern region, in all states. Saunders and Dorr (2022) point out the occurrence of this species in the states of Minas Gerais and Rio de Janeiro, however, after an intense study of the botanical collections in Brazil and abroad, no specimen was found so that this data could not be validated. This species primarily inhabits caatinga vegetation, but in the state of Rio Grande do Norte, it was observed growing in restinga vegetation (savannalike formation with beach sands deposited during the Quaternary, in areas above sea level that support scattered clumps of small trees, shrubs, herbs, and grasses (Thomas and Barbosa 2008)), an environment where W. marielleae has not been recorded.…”
Section: Morphological Affinitiesmentioning
confidence: 96%
“…In Brazil, W. rotundifolia occurs only in the northeastern region, in all states. Saunders and Dorr (2022) point out the occurrence of this species in the states of Minas Gerais and Rio de Janeiro, however, after an intense study of the botanical collections in Brazil and abroad, no specimen was found so that this data could not be validated. This species primarily inhabits caatinga vegetation, but in the state of Rio Grande do Norte, it was observed growing in restinga vegetation (savannalike formation with beach sands deposited during the Quaternary, in areas above sea level that support scattered clumps of small trees, shrubs, herbs, and grasses (Thomas and Barbosa 2008)), an environment where W. marielleae has not been recorded.…”
Section: Morphological Affinitiesmentioning
confidence: 96%
“…Subsequent to his exhaustive review, the names Ayenia magna L., A. tomentosa L., and Byttneria scabra L. were typified by Dorr & Wiersema (2010); M. tomentosa L. was typified by Moraes & al. (2013); and W. angustifolia L. was typified by Saunders & Dorr (2022). Three Linnaean Byttnerioideae species names currently lack types and they are discussed and typified here: H. triphylla L., Melochia supina L., and T. augustum L. The lectotypification of H. triphylla fixes the application of this name as a species of Fabaceae and necessitates a new combination into Lotononis (DC.)…”
Section: Introductionmentioning
confidence: 99%